Efektivitas Metode Al-Baghdadi sebagai Metode Pembelajaran Al-Qur'an: Studi Kasus di TPQ Mutiara Surga, Padang - Intan Suci Ramadani; Lathiva Wulandari; Gusmaneli (Jurnal Kajian Islam dan Sosial Keagamaan, 2024)
This article discusses the implementation of the Al-Baghdadi method in teaching Qur'anic reading at Taman Pendidikan Al-Qur'an (TPQ) Mutiara Surga, located in RT 01 RW 09, Batipuh Panjang Village. The TPQ aims to improve Qur'anic reading skills among local children. Although TPQ Mutiara Surga has adopted the Al-Baghdadi method, there is a need to identify challenges and potential in its implementation. This article focuses on the adaptability of this method within the TPQ setting, its effectiveness in enhancing Qur'anic reading skills, and its application in students' learning. A qualitative approach was used in this study, employing data collection methods such as teacher interviews, observation, and documentation. The findings reveal that the Al-Baghdadi method is implemented using the Qo'idah Baghdadiyah Ma'a Juz 'Amma textbook. The teaching process begins with the introduction of Hijaiyah letters and progresses to the reading of Juz 'Amma and the Qur'an. Teachers find this method effective, as demonstrated by the students’ fluent and proficient Qur'anic reading skills. This article is expected to contribute to the development of effective Qur'anic teaching strategies in similar environments and to provide insights for similar educational institutions.